Automated Extraction of DIBs from Cool Star Spectra. Issue Volume 9:Issue S297(2013) (21st February 2014) - Chen, H.-Ch.; Lallement, R.; Puspitarini, L.; Bonifacio, P.; Babusiaux, C.; Hill, V.
Abstract: We have developed a method allowing to extract DIBs from cool star spectra, based on combinations of stellar synthetic, telluric transmission (when necessary), and DIB profile models. It is applicable when the star temperature, surface gravity and metallicity have been previously estimated. Such a method aims at extracting extensive data from stellar spectroscopic surveys such as the Gaia-ESO Survey in progress at the VLT. The method has been applied to several strong DIBs detected towards stars from various programs and located at various distances from the solar neighborhood to the Galactic Bulge. Here we illustrate the extraction of the 8620 Å DIB, and compare its strength to the one of the 6284 Å band, both for nearby and bulge stars.